Distribution of Vaginal and Gut Microbiome in Advanced Maternal Age - Huang, Yuxin; Li, Dianjie; Cai, Wei; Zhu, Honglei; Shane, Mc Intyre; Liao, Can; Pan, Shilei (Frontiers in Cellular and Infection Microbiology, 2022)
The distribution of the microbiome in women with advanced maternal age (AMA) is poorly understood. To gain insight into this, the vaginal and gut microbiota of 62 women were sampled and sequenced using the 16S rRNA technique. These women were divided into three groups, namely, the AMA (age ≥ 35 years, n = 13) group, the non-advanced maternal age (NMA) (age < 35 years, n = 38) group, and the control group (non-pregnant healthy women, age >35 years, n = 11). We found that the alpha diversity of vaginal microbiota in the AMA group significantly increased. However, the beta diversity significantly decreased in the AMA group compared with the control group. There was no significant difference in the diversity of gut microbiota among the three groups. The distributions of microbiota were significantly different among AMA, NMA, and control groups. In vaginal microbiota, the abundance of Lactobacillus was higher in the pregnant groups. Bifidobacterium was significantly enriched in the AMA group. In gut microbiota, Prevotella bivia was significantly enriched in the AMA group. Vaginal and gut microbiota in women with AMA were noticeably different from the NMA and non-pregnant women, and this phenomenon is probably related to the increased risk of complications in women with AMA.